Internalized weight bias in the relationship between mental health and obesity in UK adolescents. (20th October 2021) - Creese, H; Saxena, S; Nicholls, D; Pascual-Sanchez, A; Hargreaves, D
Abstract: Background: It is crucial to promote mental and physical health during adolescence to protect against lifetime risks of mental health problems and obesity. Internalized weight bias (self-directed stigmatizing attitudes about perceived weight status) and bullying are implicated as potential mechanisms in the relationship between mental health and obesity in adolescence. We examined internalized weight bias and bullying as potential mediators of the relationship between mental health and weight status across adolescence in the United Kingdom (UK). Methods: We analysed data on 8, 688 adolescents from the UK Millennium Cohort Study. Weight status was defined using sex and age specific International Obesity Taskforce cut points for body-mass index (not overweight/obese; overweight; obese) at 11 and 17 years. Mental health was defined using parental reported emotional (anxiety and depression), and externalizing (aggression and impulsivity) symptoms at 11 and 17 years (low; moderate; high). Self-reported measures of internalized weight bias captured via body-dissatisfaction and self-esteem and bullying at 14 years were tested as mediators. We used Generalized Structural Equation Models to examine longitudinal pathways between weight status and mental health across 11 and 17 years, whilst accounting for concurrent associations and potential confounders. Results: Adolescents with high emotional (relative risk (RR) 1.98, 95% CI 1.28 to 3.07) or externalizing symptoms (RR 2.07, 95% CI 1.23 to 3.48) at 11 years were twice as likely to be obese at 17 years compared with those who had low symptoms. The impact of emotional and externalizing symptoms on weight status was found to be partially attributable to internalized weight bias, but not bullying, with significant mediation for body-dissatisfaction and low self-esteem. Conclusions: Internalized weight bias partially explains the relationship between mental health and weight status across adolescence. Key messages: There is a need for a holistic, early prevention strategy to focus on reducing weight stigma to encourage healthy mental and physical development of children. The relationship between mental health and weight status across adolescence is partly attributable to internalized weight bias.